An adaptive approach for optimized opportunistic routing over Delay Tolerant Mobile Ad hoc Networks - Zhao, Xiaogeng (Rhodes University, Faculty of Science, Department of Computer Science, 2008)
This thesis presents a framework for investigating opportunistic routing in Delay Tolerant Mobile Ad hoc Networks (DTMANETs), and introduces the concept of an Opportunistic Confidence Index (OCI). The OCI enables multiple opportunistic routing protocols to be applied as an adaptive group to improve DTMANET routing reliability, performance, and efficiency. The DTMANET is a recently acknowledged networkarchitecture, which is designed to address the challenging and marginal environments created by adaptive, mobile, and unreliable network node presence. Because of its ad hoc and autonomic nature, routing in a DTMANET is a very challenging problem. The design of routing protocols in such environments, which ensure a high percentage delivery rate (reliability), achieve a reasonable delivery time (performance), and at the same time maintain an acceptable communication overhead (efficiency), is of fundamental consequence to the usefulness of DTMANETs. In recent years, a number of investigations into DTMANET routing have been conducted, resulting in the emergence of a class of routing known as opportunistic routing protocols. Current research into opportunistic routing has exposed opportunities for positive impacts on DTMANET routing. To date, most investigations have concentrated upon one or other of the quality metrics of reliability, performance, or efficiency, while some approaches have pursued a balance of these metrics through assumptions of a high level of global knowledge and/or uniform mobile device behaviours. No prior research that we are aware of has studied the connection between multiple opportunistic elements and their influences upon one another, and none has demonstrated the possibility of modelling and using multiple different opportunistic elements as an adaptive group to aid the routing process in a DTMANET. This thesis investigates OCI opportunities and their viability through the design of an extensible simulation environment, which makes use of methods and techniques such as abstract modelling, opportunistic element simplification and isolation, random attribute generation and assignment, localized knowledge sharing, automated scenario generation, intelligent weight assignment and/or opportunistic element permutation. These methods and techniques are incorporated at both data acquisition and analysis phases. Our results show a significant improvement in all three metric categories. In one of the most applicable scenarios tested, OCI yielded a 31.05% message delivery increase (reliability improvement), 22.18% message delivery time reduction (performance improvement), and 73.64% routing depth decrement (efficiency improvement). We are able to conclude that the OCI approach is feasible across a range of scenarios, and that the use of multiple opportunistic elements to aid decision-making processes in DTMANET environments has value.
Keywords: Ad hoc networks (Computer networks); Computer network architectures; Computer networks; Routing protocols (Computer network protocols)